Imported Inflation in South Africa: An Empirical Study - Kevin Nell (University of Kent, Department of Economics, 2000)
The main objective of this paper is to analyse the inflationary impact of exchange rate depreciation in South Africa over the period 1984-1998 when the monetary authorities adopted a more market-oriented exchange rate system. Although the empirical part of the paper extensively focuses on this period, the analysis also concentrates on the period 1973-1983 to determine whether the underlying causes of inflation have changed following significant structural, political and institutional changes. From a macroeconomic perspective, the empirical results show that the long-run causes of inflation in South Africa have changed from a demand-pull inflation over the period 1973-1983, to a cost-push cause (import prices and wage rate changes) of inflation since 1987 when a market determined exchange rate finally stabilised.
Keywords: C22; E24; E31; 330; Imported inflation; Import Pass-through; Exchange rate; Phillips curve; Inflationskonvergenz; Wechselkurspolitik; Südafrika